1998
DOI: 10.1521/soco.1998.16.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Choose Your Poison: Effects of Lay Beliefs About Mental Processes on Attitude Change

Abstract: Lay theories about persuasive messages were expected to lead to unwanted changes in attitudes that people were trying to protect. In Study 1 , students opposed to the legalization of marijuana chose to watch either a pro-legalization speech or a pro-legalization subliminal message, with instructions to choose the tape that would influence them the least. A significant proportion of people chose the speech. Among these participants and those randomly assigned to watch the tapes, however, the speech caused signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…One, with which we readily concur, is that lay theories of the effectiveness of suasory appeals may bear little correspondence to what is actually persuasive. Asking individuals to judge message effectiveness may prompt evaluations based on simplistic or erroneous beliefs about message impact (Wilson, Houston, & Meyers, 1998).…”
Section: Critique Of Pementioning
confidence: 99%
“…One, with which we readily concur, is that lay theories of the effectiveness of suasory appeals may bear little correspondence to what is actually persuasive. Asking individuals to judge message effectiveness may prompt evaluations based on simplistic or erroneous beliefs about message impact (Wilson, Houston, & Meyers, 1998).…”
Section: Critique Of Pementioning
confidence: 99%
“…As previous researchers have argued (Henrikson & Flora, 1999), perhaps skepticism about being influenced by persuasion attempts might actually make people more vulnerable to these tactics. Customers who dismiss the ability of selling methods to influence them might be less alert to persuasion attempts or might not make an effort to avoid being exposed to these attempts and thus are more susceptible to their influence (e.g., Wilson, Houston, & Meyers, 1998). However, it might also be suggested that an accepting attitude toward persuasion attempts makes people more susceptible to their influence (Tal-Or, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…If participants complain that the intervention was a waste of time or worse, insulting and demeaning, the designers of that intervention should obviously take note. But, it is a near truism in social psychology that participants are not always the best authority to assess how much their attitudes and beliefs have changed (Bem & McConnell, 1970;Goethals & Reckman, 1973;Wilson, Houston, & Meyers, 1998). Further, because an intervention made people feel uncomfortable or bored does not necessarily mean it failed to change their attitudes and beliefs.…”
Section: The Power Of the Experimental Method: Let Us Export Itmentioning
confidence: 99%